Education Through Poster Media “Flu Is Not The Same as The Common Cold” For Patients at Azim Farma Pharmacy - Gandis Larasati; Diana Ramatillah; Kashif Khan (Journal of Community Development, 2026)
Myths and misconceptions about flu and the common cold are widespread in society, including the assumptions that flu is the same as the common cold, that influenza vaccination causes illness, or that flu is only a mild illness. These myths are suspected to affect the ability to differentiate between the two illnesses. This counseling activity aims to provide education about the differences between influenza and the common cold, their appropriate management, and to correct misconceptions and myths circulating within the community.. The session was held on Sunday, November 30, 2025, from 10:30 AM to 12:30 PM WIB. The primary target of this counseling was patients at Azim Farma Pharmacy, with a target of 82 participants. The method of implementation was in the form of direct face-to-face interaction, providing education using poster media. The success indicator was measured by comparing pre-test and post-test scores. The results of the activity showed that before the education was given, the majority of respondents (34 respondents, 41.5%) were in the good knowledge category. After the education, the majority (64 respondents, 75.6%) were in the good knowledge category, indicating that the counseling participants were able to receive and understand the information and knowledge well. Statistical analysis using the Wilcoxon test on these results yielded a p-value = 0.000 (p < 0.05), indicating a significant difference before and after the education. This shows that overall, the intervention can be considered successful in improving respondents' understanding of the difference between influenza and the common cold. This counseling has positive implications for health education and promotion efforts in increasing public awareness in differentiating and managing coughs and colds.